Identifikasi Akuifer Dangkal dan Akuifer Dalam dengan Metode Geolistrik (Kasus: Di Kecamatan Masaran) - D Darsono (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2016)
Identification of aquifer layer location has been done using Schlumberger configuration of geoelectric resistivity methods in Masaran District. Data collection was performed using resistivity meter OYO Mc-el-ohm series 2119c having a length of current electrode (AB / 2) from 1.5 m to 350 meters. Data processing was done using software IP2win. The purpose of this study was to identify the location of confined aquifer and unconfined aquifer. The result showed that litology of aquifer layers were detected as clayed sand, sands and gravel sands. The depth of confined aquifer was detected for TS1 (4.52 meters to 8.57 meters and 22.4 meters to 34 meters), TS2 (8.84 meters to 20.9 meters), TS3 (2.87 meters to 10 meters and 13.3 meters to 41.5 meters), TS4 (20.09 meters to 6.71 meters and 17.3 meters to 36.4 meters) and TS5 (6.3 meters to 25 meters). The thickest layer of confined aquifer was TS3. While, the depth of unconfined aquifer was detected for TS1 (68.1 meters to 78 meters and 94.3 meters to 115 meters), TS2 (36.9 meters to 93.4 meters and 103 meters to 134 meters), TS3 (72.8 meters to 101 meters), TS4 (46.3 meters to 67.5 meters and 82.1 meters to 98 meters), and TS5 (50.1 meters to 93.5 meters and 99.7 meters to 111 meters). The layer thickness of unconfined aquifer were detected for TS1 (30.6 meters), TS2 (86.7 meters), TS3 (28.4 meters), TS4 (37 meters), and TS5 (55 meters). The layer thickness of unconfined aquifer that has the thickest was TS2.